PARADIGMA PENEGAKAN HUKUM PIDANA TERHADAP PENAMBANGAN ILEGAL DI LAHAN PASCA TAMBANG DI BANGKA BELITUNG (Faculty of Law, University of Palembang, 2024)
Law enforcement against mining activities in Bangka Belitung, especially illegal mining, is an urgency that must be carried out in order to maintain balance and environmental ecosystems. Reclamation efforts are part of post-mining activities that cannot be separated from the responsibilities of mining actors as legally implemented as stipulated in Law Number 3 of 2020 (UU No. 3 of 2020) concerning Amendments to Law number 4 of 2009 concerning Mineral Mining and Coal. (UU No. 4 of 2009) and specifically regulated in Government Regulation Number 78 of 2010 concerning Reclamation and Postmining (PP RI No.78 of 2010). The purpose of this study is to analyze the effectiveness of law enforcement against mining activities both in pre-mining activities to reclamation and post-mining activities based on several related regulations. This type of research is using normative juridical research. The implementation of reclamation efforts in Bangka Belitung, which is the obligation of mining actors, has not been fully realized. This is based on the lack of supervision from the authorities and the factors that trigger rampant illegal mining activities. Illegal mining carried out in Jurung Village, Bangka Regency, Bangka Belitung Islands, even on reclamation and post-mining land. Keywords: Law Enforcement; Mining; Reclamation